2016
DOI: 10.1111/jpet.12161
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Public Good Provision with Anonymous Contributors

Abstract: We analyze a static game of public good contributions where finitely many anonymous players have heterogeneous preferences about the public good and heterogeneous beliefs about the distribution of preferences. In the unique symmetric equilibrium, the only individuals who make positive contributions are those who most value the public good and who are also the most pessimistic; that is, according to their beliefs, the proportion of players who most like the public good is smaller than it would be according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The literature on voluntary contributions to a public goods has many applications, such as mutual insurance pools (Levy‐Garboua, Montmarquette, Valksmann, & Villeval, ) and anonymous contributors (Maldonado & Rodrigues‐Neto, ), and has been enriched by the theory of clubs (Wooders, ) and by additional considerations such as group structure (Lind, ) and public norm enforcement (Buchholz, Falkinger, & Rübbelke, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on voluntary contributions to a public goods has many applications, such as mutual insurance pools (Levy‐Garboua, Montmarquette, Valksmann, & Villeval, ) and anonymous contributors (Maldonado & Rodrigues‐Neto, ), and has been enriched by the theory of clubs (Wooders, ) and by additional considerations such as group structure (Lind, ) and public norm enforcement (Buchholz, Falkinger, & Rübbelke, ).…”
mentioning
confidence: 99%
“…The generalization of our model to the case of heterogeneous agents with warm glow is left for future research. For (non‐warm‐glow) models of voluntary contributions to public goods when individuals are heterogeneous and have imperfect information, see Bac and Bag () and Maldonado and Rodrigues‐Neto ().…”
mentioning
confidence: 99%
“…In voting environments in which the set of alternatives is a metric space and each agent's preference is represented by a continuous utility function, they showed that, if the social choice function satisfies strategy-proofness and its range contains at least three alternatives, 1 See Clarke (1971), Moulin (1994), and Serizawa (1996Serizawa ( , 1999 for nonexcludable public good economies. In addition, see Caplan (2016), Maldonado and Rodrigues-Neto (2016), and Bhattacharya, Tokovenko, and Sardana (2017) for recent theoretical studies on nonexcludable public good economies.…”
Section: Introductionmentioning
confidence: 99%
“…See Clarke (), Moulin (), and Serizawa (, ) for nonexcludable public good economies. In addition, see Caplan (), Maldonado and Rodrigues‐Neto (), and Bhattacharya, Tokovenko, and Sardana () for recent theoretical studies on nonexcludable public good economies. …”
mentioning
confidence: 99%
“…Unlike other recent papers on public good theory (see, e.g., Barbieri & Malueg, 2016; Caplan, ; Maldonado & Rodrigues‐Neto, ), complete certainty and full information are assumed in our model.…”
mentioning
confidence: 99%